Multidimensional first-order dominance comparisons of population wellbeing - Channing Arndt; Nikolaj Siersbæk; Lars Peter Østerdal (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
In this paper, we convey the concept of first-order dominance (FOD) with particular focus on applications to multidimensional population welfare comparisons. We give an account of the fundamental equivalent definitions of FOD, illustrated with simple numerical examples. An implementable method for detecting dominances is explained along with a bootstrapping procedure that yields additional information relative to what can be obtained from dominance comparisons alone. We discuss strengths and weaknesses of FOD, compared to other multidimensional population comparison concepts, and describe practical tools that enable the reader to easily use it.
Keywords: I31; I32; D30; 330; multidimensional welfare; multidimensional wellbeing; first-order dominance